CALCULATION OF THE THERMAL FIELD AND THE THERMAL RESISTANCE OF BUILDINGS ENVELOPES USING THE FINITE ELEMENT METHOD - U. U. Liashkevich (Системный анализ и прикладная информатика)
The method of calculation the thermal field and the thermal resistance of fragments of building envelope and developed computer calculating program are described in the article «Calculation of the thermal field and the thermal resistance of buildings envelopes using the finite element method». The main logical modules of the program are described. An example of calculation of temperature field and of the thermal resistance of element of monolithic frame building is given.